A challenging interpretation of a hexagonally layered protein structure. (1st January 2014) - Thompson, Michael C.; Yeates, Todd O.
<x xml:space="preserve">Abstract</x> The carboxysome is a giant protein complex that acts as a metabolic organelle in cyanobacteria and some chemoautotrophs. Its outer structure is formed by the assembly of thousands of copies of hexameric shell protein subunits into a molecular layer. The structure determination of a CcmK1 shell protein mutant (L11K) from the β‐carboxysome of the cyanobacterium Synechocystis PCC6803 led to challenges in structure determination. Twinning, noncrystallographic symmetry and packing of hexameric units in a special arrangement led to initial difficulties in space‐group assignment. The correct space group was clarified after initial model refinement revealed additional symmetry. This study provides an instructive example in which broken symmetry requires a new choice of unit‐cell origin in order to identify the highest symmetry space group. An additional observation related to the packing arrangement of molecules in this crystal suggests that these hexameric shell proteins might have lower internal symmetry than previously believed.